Effects of Sea-Surface Temperature, Cloud Vertical Structure and Wind Speed on Temperature Change between Hiatus and Post-Hiatus Periods in Tropical Western Pacific - Chien-Han Su; Jean-Fu Kiang (Atmosphere, 2022)
A region in the tropical western Pacific is selected to study the notable change in temperature between the recent warming hiatus period and the post-hiatus period. In total, three probable factors, namely sea-surface temperature (SST), cloud vertical structure (CVS) and wind speed, which may account for the temperature change are found to exhibit noticeable differences between these two periods. A one-dimensional atmospheric radiative transfer model, incorporating convective adjustment and energy exchange with the ocean, is developed to simulate the diurnal pattern of temperature profile under the influence of the three probable factors in the two concerned periods. Virtual profiles of sea-surface temperature, cloud vertical structure and wind speed in both periods are developed from data available in the literature. Diurnal patterns of temperatures near the air–sea interface are computed with the proposed model over a sufficient number of days. The simulated temperatures under different combinations of factors, in either the hiatus or post-hiatus period, are statistically analyzed to gain insights about the separate and combined effects of these three factors on causing climate change.